Inferior Vena Cava and Renal Vein Thrombosis Associated with Thymic Carcinoma - Vlad Teodor Berbecar; Roxana Jurubita; Marina Paraschiv; Bogdan Obrisca; Bogdan Sorohan; Gener Ismail (Case Reports in Medicine)
Thymic tumors are rare mediastinal tumors that can present with a wide variety of symptoms. They can cause distant manifestations and are frequently associated with paraneoplastic syndromes. In our case, we describe the evolution of a 68-year-old male whose first manifestation was thrombosis of the inferior vena cava and renal veins. Thrombosis of large abdominal veins is rare, especially without being associated with any other comorbidity or risk factors.